Kelas Kita Based Blended Learning: Biology Learning Model to Improve Student Activities, Attitudes, and Achievements - Anda Juanda; Kartimi Kartimi; Dessy Indriani; Dindin Nasrudin (Jurnal Pendidikan Sains Indonesia, 2020)
In the current era of technological development, the flow of information and knowledge is very quickly updated, so that facilities are needed to compensate, especially in the field of education. Conventional learning models can support interactions between teachers and students, but on the other hand, this model is less able to provide facilities in the form of access to information anytime and anywhere. These weaknesses can be overcome by online learning, so that a blended learning solution appears, which still considers the interaction of teachers and students and expands learning opportunities because it is not limited to time and place. This study aimed to determine the effectiveness of blended learning based on kelas kita network sites in improving student achievement, activities, and learning attitudes. The subjects of this study were two classes of MA students (experimental class of 33 students and control class of 34 students) in Cirebon, Indonesia. The biological material chosen in this study was environmental change. The study design used a Pretest-Posttest control group. Data collection techniques employed observation, tests, and questionnaires. From the results of the study, it provides information that the experimental class applied blended learning model had significantly different achievements, activities, and learning attitudes (sig 0.05) compared to the control class. Students had an enthusiastic attitude because they were given the opportunity to explore their potential in studying literature based on kelas kita network. The implication of this research is that a blended learning model can be developed and applied to other materials, even in other subjects.